ANALISIS KINERJA STRUKTUR PADA GEDUNG BERTINGKAT DENGAN ANALISIS PUSHOVER BERDASARKAN ATC-40: ANALISIS KINERJA STRUKTUR PADA GEDUNG BERTINGKAT DENGAN ANALISIS PUSHOVER BERDASARKAN ATC-40 - Kukuh Kurniawan Dwi Sungkono; Krisdianti, Ega Ayu; Gunarso, Gunarso (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2024)
Indonesia is an area prone to earthquakes. Earthquakes can cause infrastructure damage and casualties. Efforts are needed to reduce the risk of earthquake hazards by strengthening earthquake-resistant infrastructure. The design procedures for earthquake-resistant buildings are carried out using a performance-based design approach. Building performance can be estimated through non-linear static pushover analysis. This research takes a case study in Jongke Market, Surakarta. This research aims to determine the capacity curve, performance level, and structure collapse mechanism. The method used is pushover analysis with the capacity spectrum. The result of this analysis is a capacity curve that processed to determine the level of structure performance referring to the drift ratio limitation table in the Applied Technology Council (ATC-40). Based on the results of this research, displacement that occurred in the x direction is 92 mm and in the y direction is 77 mm. Building displacement is good because the displacement that occurred is smaller than the displacement limit (control). The total maximum drift in the x direction is 0.007 and in the y direction is 0.006. The maximum inelastic total drift in the x direction is 0.005 and in the y direction is 0.004. Based on the drift ratio limitation table in the ATC-40 document, this building has an immediate occupancy performance level. Based on the plastic hinge mechanism formed, the existing structure also meets the ideal collapse concept (strong column-weak beam).